(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Ulcer bleeding in patients with liver cirrhosis represents one of the most challenging clinical problems in emergency gastroenterology and surgery. Its course is complicated by portal hypertension, coagulation disorders, reduced regenerative potential of the liver, and a high risk of infectious complications. According to studies, mortality in ulcer bleeding among cirrhotic patients is 2–3 times higher than in patients without comorbid pathology, reaching 20–40%. These patients often experience recurrent bleeding, multiple organ failure, and unfavorable outcomes. Differential diagnosis of the bleeding source in this category of patients is difficult due to the similarity of clinical manifestations of peptic ulcer disease with bleeding from esophageal and gastric varices. This necessitates the improvement of diagnostic algorithms with the use of endoscopic, laboratory, and instrumental methods. Optimization of management strategies should be aimed not only at achieving local hemostasis but also at correcting coagulopathies, reducing portal pressure, and controlling systemic inflammation. The application of combined endoscopic hemostasis methods in combination with rational drug therapy can significantly reduce the risk of rebleeding and mortality. Thus, the development and implementation of optimized approaches to the diagnosis and treatment of ulcer bleeding in patients with liver cirrhosis is a highly relevant task of modern clinical practice.